Effect of diamond-like carbon thin film coated acrylic resin on candida albicans biofilm formation - Queiroz, José Renato Cavalcanti; Fissmer, Sara Fernanda; Koga-Ito, Cristiane Yumi [UNESP]; Salvia, Ana C. R. D. [UNESP]; Massi, Marcos; Sobrinho, Argermiro Soares da Silva; Júnior, Lafayette Nogueira [UNESP] (Wiley, 2013)
Purpose: The purpose of this study was to evaluate the effect of diamond-like carbon thin films doped and undoped with silver nanoparticles coating poly(methyl methacrylate) (PMMA) on Candida albicans biofilm formation. The control of biofilm formation is important to prevent oral diseases in denture users. Materials and Methods: Forty-five PMMA disks were obtained, finished, cleaned in an ultrasonic bath, and divided into three groups: Gc, no surface coating (control group); Gdlc, coated with diamond-like carbon film; and Gag, coated with diamond-like carbon film doped with silver nanoparticles. The films were deposited using a reactive magnetron sputtering system (physical vapor deposition process). The specimens were characterized by optical profilometry, atomic force microscopy, and Rutherford backscattering spectroscopy analyses that determined differences in chemical composition and morphological structure. Following sterilization of the specimens by γ-ray irradiation, C. albicans (ATCC 18804) biofilms were formed by immersion in 2 ml of Sabouraud dextrose broth inoculated with a standardized fungal suspension. After 24 hours, the number of colony forming units (cfu) per specimen was counted. Data concerning biofilm formation were analyzed using ANOVA and the Tukey test (p < 0.05). Results: C. albicans biofilm formation was significantly influenced by the films (p < 0.00001), reducing the number of cfu, while not affecting the roughness parameters (p > 0.05). The Tukey test showed no significant difference between Gdlc and Gag. Films deposited were extremely thin (∼50 nm). The silver particles presented a diameter between 60 and 120 nm and regular distribution throughout the film surface (to Gag). Conclusion: Diamond-like carbon films, doped or undoped with silver nanoparticles, coating the base of PMMA-based dentures could be an alternative procedure for preventing candidosis in denture users. © 2013 by the American College of Prosthodontists.
Keywords: AFM; Complete denture; Denture base; DLC; Magnetron sputtering; Nanoparticles; Plasma; Profilometry; RBS